Wpływ masy ciała na ciśnienie tętnicze krwi = Effect of weight in blood pressure patients - Nalepa, Dorota; Weber, Dorota; Rogala, Renata; Charzyńska–Gula, Marianna (Journal of Education, Health and Sport, 2015)
Nalepa Dorota, Weber Dorota, Rogala Renata, Charzyńska–Gula Marianna. Wpływ masy ciała na ciśnienie tętnicze krwi = Effect of weight in blood pressure patients. Journal of Education, Health and Sport. 2015;5(11):85-98. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33443 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A85-98 https://pbn.nauka.gov.pl/works/667125 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. WPŁYW MASY CIAŁA NA CIŚNIENIE TĘTNICZE KRWI EFFECT OF WEIGHT IN BLOOD PRESSURE PATIENTS Dorota Nalepa1, Dorota Weber2, Renata Rogala3, Marianna Charzyńska–Gula4 1. Oddział Neurologii Wojewódzkiego Szpitala Specjalistycznego im. Kardynała Stefana Wyszyńskiego w Lublinie, doktorantka studiów doktoranckich Uniwersytetu Medycznego w Lublinie, adres email: nalepad1@wp.pl 2. Absolwentka Kierunku Pielęgniarstwo Warszawski Uniwersytet Medyczny 3. Doktorantka studiów doktoranckich Uniwersytetu Medycznego w Lublinie 4. Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu Streszczenie Cel. Ocena wpływu masy ciała na ciśnienie tętnicze krwi pacjentów leczonych z powodu nadciśnienia. Materiał i metody. Badania nad podjętą problematyką zostały przeprowadzone w Oddziale Kardiologii Samodzielnego Publicznego Szpitala Klinicznego Nr 4, przy ulicy Jaczewskiego w Lublinie, od grudnia 2014 do lutego 2015 roku. Respondenci wypełnili 100 kwestionariuszy, z czego wszystkie zostały zakwalifikowane do analizy statystycznej. W badaniach wykorzystano technikę ankiety audytoryjnej, oraz dokonano pomiarów ciśnienia tętniczego, obwodów ciała, masy ciała i wyliczono BMI. Wyniki. Nadmierna masa ciała jest z jednym z czynników ryzyka sercowo-naczyniowego. Przyczynia się ona nie tylko do rozwoju nadciśnienia tętniczego, ale także do zaburzeń metabolicznych, takich jak: insulinooporność, hiperinsulinemia, zaburzenia lipidowe oraz cukrzyca. W badaniach własnych wykazano u 37% ankietowanych nadwagę, a u 34% otyłość. Otyłość brzuszną stwierdzono u ponad 1/3 mężczyzn i ponad połowy kobiet, na granicy wartości progowej znajduje się około 1/5 mężczyzn i blisko 1/4 kobiet. Wnioski. W analizie szczegółowej zachowań wśród grupy badanych pacjentów wskazano najważniejsze kierunki działań, które powinny stać się dla nich priorytetowe: - edukacja w zakresie normalizacji masy ciała, postępowania dietetycznego w nadciśnieniu tętniczym oraz zalecenie aktywności fizycznej, - wskazanie korzyści wypływających z podjętych działań, przekonanie badanych o ich własnej wartości, możliwości zmiany i zachęcenie do podjęcia działań w tym kierunku oraz poszukiwanie stymulacji ze strony otoczenia w celu podtrzymywania pożądanych zachowań. Słowa kluczowe: nadciśnienie tętnicze, otyłość. Abstract Aim. Assessment of the impact body weight on blood pressure patients treated for hypertension. Material and methods. Research on issues taken were carried out in the Department of Cardiology of the Independent Public Clinical Hospital No. 4, Street Jaczewskiego in Lublin, from December 2014 to February of 2015. The interviewers completed 100 questionnaires, of which all were accepted for statistical analysis. The study used a technique audit questionnaire and measurements of blood pressure, circuits, weight, BMI. Results. Excessive body weight is one of the factors of cardiovascular risk. It contributes not only to the development of hypertension, but also metabolic disorders such as insulin resistance, hyperinsulinemia, lipid disorders and diabetes. In our study, 37% of respondents are overweight and 34% obese. Abdominal obesity was found in more than 1/3 of men and over half of the women, on the border of the threshold value is about 1/5 of men and nearly 1/4 of women. Conclusions. The detailed analysis of the examined behavior among groups of patients should identify the most important directions of activities that are a priority in the study group: - education in standardization body weight, dietary hypertension and physical activity recommendation - indication benefits of the actions taken, the conviction of respondents for their self-esteem, ability to change and to encourage action in this direction, and seeking stimulation from the environment in order to sustain the desired behavior. Keywords: hypertension, blood pressure.